100 things you should known about British History - Steele, Philip; Miles Kelly Publishing; Macdonald, Fiona (Miles Kelly Publishing Ltd: Essex, 2004)
Here, history has been recreated with exactly 100 facts. Readers will be absorbed by the fun activities such as projects and quizzes and there are cartoons to add a lighter touch.
Keywords: Great Britain History